Taxonomy of Tools at BIBB - Güntürk-Kuhl, Betül [Verfasser]; Lewalder, Anna Cristin [Verfasser]; Martin, Philipp [Verfasser] (My University, 2020)
"This article presents the basic concept of the work tools taxonomy of the Federal Institute for Vocational Education and Training (BIBB). Work tools are defined as tangible and intangible objects, used by a person or a machine to perform a task. By an automated operation the work tools were extracted from the digital job advertisements provided by the Federal Employment Agency. The Taxonomy consists of eight main categories which are divided into four levels. The category system is continuously updated. It completely covers the range of work tools in its basic structure. The method of automated extraction and automated categorization can also be applied to different data sets and thus can be transferred to different scientific issues." (authors' abstract; BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; Arbeitsmittel; Digitalisierung; Automatisierung; Software; Stellenanzeige; Analyse